The role of cutaneous manifestations in the diagnosis of the Ehlers‐Danlos syndromes. Issue 1 (15th July 2022) - Stembridge, Natasha; Doolan, Brent J.; Lavallee, Mark E.; Hausser, Ingrid; Pope, F. Michael; Seneviratne, Suranjith L.; Winship, Ingrid M.; Burrows, Nigel P.
Abstract: The Ehlers‐Danlos syndromes (EDS) comprise a group of inherited connective tissue disorders presenting with features of skin hyperextensibility, joint hypermobility, abnormal scarring and fragility of skin, blood vessels and some organs. The disease is generally diagnosed through the cluster of clinical features, though the addition of genetic analysis is the gold standard for diagnosis of most subtypes. All subtypes display skin manifestations, which are essential to the accurate clinical diagnosis of the condition. Furthermore, cutaneous features can be the first and/or only presenting feature in some cases of EDS and thus understanding these signs is vital for diagnosis. This review focuses on particular cutaneous features of each EDS subtype and their clinical importance. Provision of a specific diagnosis is important for management, prognosis and genetic counselling, often for family members beyond the individual. Abstract :